Pemanfaatan Mikrohidro Untuk Membangun Desa Mandiri Energi - M. Kudeng Sallata; Hunggul Yudono SHN; Abd. Kadir Wakka (Foresty Faculty of Hasanuddin University, 2015)
To enhance active participation of local communities in forest management, the benefit of forest services to fulfill their basic need should be maximized. This research has been carried out to examine the potential of forest and the village to be an energy self-sufficient village. The specific objectives of the research are to: 1) acquiring data of village potential for microhydro development, 2) establishing a microhydro installation by maximizing the benefit of water power, and 3) acquiring data of potential impact of microhydro development on well local community participation and awareness. The research methods were direct observation, interviews and descriptive analysis. Based on field situation, the design and manufacture of turbine engine has been assembled to produce electricity of 10 KVA. Consumers were 131 households allied in group to operate the microhydro properly. The establishment of microhydro have enhanced positive perception on forest-water yield, collective participation, awareness and sense of ownership of the villagers to forest ecosystem.